Re-writing the Sustainable Development Goals from marketplaces in Argentina, Chile, Colombia and Mexico - Clausen, Helene Balslev; Velázquez García, Mario Alberto (Diálogos Latinoamericanos, 2019)
The aim of this paper is to reflect on Sustainable Development Goals (SDGs) and informality which is an economy not acknowledged within the SDGs. Based on anthropological fieldwork the article analyzes how informal, diverse economies in this case, marketplaces in different Latin American countries, might contribute to elaborate and rewrite sustainable development models. Throughout history, marketplaces in Latin America have provoked strong political debates because they operate in the informal sector and now they are increasingly being framed as tourist attractions. This creates an opportunity to reposition marketplaces as an asset in the formal economy. The informal, diverse economies constitute more than half of the GDPs in the Global South including Latin America. Despite repeated claims about the importance of informality as one of the fastest growing phenomena of our time and increasingly an issue of public and political concern, no systematic studies within tourism engages with the SDGs dealing with informality. Consequently, central to this paper is to consider integrating existing practices into SDGs to create pathways for sustainable development models.